Deteksi Mutasi A3243G MTDNA pada Penderita Diabetes Melitus Tipe 2 Menggunakan PCR Alelle’s Specific Amplification (PASA) - Lestari, Windi; Kasmuddin, Kasmuddin; Rantisari T, A. Meinar Dwi; Saleh, Adriandy (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
Type 2 diabetes mellitus is one of the most common metabolic disorders caused by a combination of two men factors: impaired insulin secretion by pancreatic β cells and the inability of insulin-sensitive tissues to respond properly to insulin. The genetically predisposed from of diabetes known as type 2 diabetes mellitus produce the ATP required for the secretory process. An A to G mutation at the 3243-nucleotide position of mitochondrial DNA tRNALeu gene is associated with damage. Maternally Inherited Diabetes and Deafness (MIDD), which was identified as the cause of the mutation, the Allele’s Specific Amplification (PASA) PCR method was chosen because it had not been widely used by other researchers and to increase detection accuracy because the A3243G mtDNA mutation is a heteropblastic mutation. The aim of th research was to detect the A3243G mtDNA mutation in type II diabetes mellitus patiens by using Allele’s Specific Amplification (PASA) PCR. This type of qualitative descriptive research. The result showed the appearance of a 200 bp band in 10 out of 15 samples amplified with D1/DN primer pairs for normal mtDNA and D1/DMt prime pairs.